Provizórikus veserákaltípusok a 2016. évi WHO-klasszifikációt követően - Jenei, Alex; Hes, Ondrej; Kuthi, Levente (Orvosi hetilap, 2020)
Renal cell carcinoma (RCC) represents a heterogenous group of malignant tumors that originate from the kidney parenchyma. The different entities have their own specific epidemiological, morphological, immunohistochemical, genetic and clinical characteristics. The new WHO classification of renal tumors was published in 2016, and it takes all of these features together into account. Although in the past three years, several emerging subtypes have been described, these are not yet included in the current classification. In this review paper, these entities are summarized in details including the following emerging subsets: thyroid-like follicular carcinoma, ALK rearrangement-associated RCC, renal cell carcinoma with prominent smooth muscle stroma, fumarate hydratase-deﬁcient RCC, biphasic squamoid papillary RCC, eosinophilic solid and cystic RCC, atrophic kidney-like RCC, clear cell RCC with giant cells and emperipolesis, Warthin-like papillary RCC, low-grade oncocytic renal tumor (CD117-negative; CK7-positive), high-grade oncocytic renal tumor, TCEB1-mutated RCC and chromophobe RCC with neuroendocrine features. These entities are mostly diagnosed as RCC unclassified. The aim of this study is to introduce these subsets to the Hungarian pathologists, oncologists and urologists, to prompt diagnostic accuracy and to facilitate a collection along with a consecutive analysis of these cases. Orv Hetil. 2020; 161(3): 83-94.
Keywords: nádory ledvin; Biomarkers, Tumor; ledviny; karcinom z renálních buněk; nádorové biomarkery; Maďarsko; Carcinoma, Renal Cell; Kidney; Humans; lidé; Kidney Neoplasms; Hungary